Nigella sativa callus treated with sodium azide exhibit augmented antioxidant activity and DNA damage inhibition - Mohammed Shariq Iqbal (Nature Portfolio, 2021)
Abstract Nigella sativa L. (NS) is an herbaceous plant, possessing phytochemicals of therapeutic importance. Thymoquinone is one of the active phytochemicals of NS that confers noteworthy antioxidant properties. Sodium azide, an agent of abiotic stress, can modulates antioxidant system in plants. In the present investigation, sodium azide (0, 5 µM, 10 µM, 20 µM, 50 µM, 100 µM and 200 µM) doses administered to the in vitro NS callus cultures for production/modification of secondary metabolites with augmented activity. 200 µM sodium azide treated NS callus exhibited maximum peroxidase activity (1.286 ± 0.101 nanokatal mg−1 protein) and polyphenol oxidase activity (1.590 ± 0.110 nanokatal mg−1 protein), while 100 µM sodium azide treated NS callus for optimum catalase activity (1.250 ± 0.105 nanokatal mg−1 protein). Further, 200 µM sodium azide treated NS callus obtained significantly the highest phenolics (3.666 ± 0.475 mg g−1 callus fresh weight), 20 µM sodium azide treated NS callus, the highest flavonoids (1.308 ± 0.082 mg g−1 callus fresh weight) and 100 µM sodium azide treated NS callus, the highest carotenes (1.273 ± 0.066 mg g−1 callus fresh weight). However, NS callus exhibited a decrease in thymoquinone yield/content vis-à-vis possible emergence of its analog with 5.3 min retention time and an increase in antioxidant property. Treatment with 200 µM sodium azide registered significantly the lowest percent yield of callus extract (4.6 ± 0.36 mg g−1 callus fresh weight) and thymoquinone yield (16.65 ± 2.52 µg g−1 callus fresh weight) and content (0.36 ± 0.07 mg g−1 callus dry weight) and the highest antioxidant activity (3.873 ± 0.402%), signifying a negative correlation of the former with the latter. DNA damage inhibition (24.3 ± 1.7%) was recorded significantly maximum at 200 µM sodium azide treatment. Sodium azide treated callus also recorded emergence of a new peak at 5.3 min retention time (possibly an analog of thymoquinone with augmented antioxidant activity) whose area exhibits significantly negative correlation with callus extract yield and thymoquinone yield/content and positive correlation with antioxidant activity and in vitro DNA damage inhibition. Thus, sodium azide treatment to NS callus confers possible production of secondary metabolites or thymoquinone analog (s) responsible for elevated antioxidant property and inhibition to DNA damage. The formation of potent antioxidants through sodium azide treatment to NS could be worthy for nutraceutical and pharmaceutical industries.